Multidrug Resistant Shigella flexneri Infection Simulating Intestinal Intussusception - Srirangaraj Sreenivasan (Journal of Laboratory Physicians, 2016)
Shigella enteritis remains an important cause of mortality and morbidity in all age groups, in developing as well as developed countries. Owing to the emerging resistance to multiple antibiotics among Shigella spp., it has been recognized as a major global public health concern and warrants constant monitoring of its resistance pattern. We report a case of segmental ileitis caused by non-ESBL producing multidrug resistant Shigella flexneri in an infant clinically mimicking intussusception, which was effectively treated by ceftriaxone.